Optimizing a diagnostic tool: coronary computed tomography angiography-guided percutaneous coronary intervention of anomalous coronary artery presenting as an acute coronary syndrome - Upadhyay, Amar Nath; Kumar, Barun (International Journal of Research in Medical Sciences, 2022)
Anomalous coronary artery presenting with acute coronary syndrome is relatively rare. Achilles heel of percutaneous coronary intervention in a such patient is difficult cannulation of the culprit artery. Coronary CT angiography provides detailed information about the origin and course of the anomalous coronary artery. A few additional information like exit angle and orifice configuration provided exclusively by CT helps in appropriate hardware selection for angiographic success.